PERLINDUNGAN HUKUM TERHADAP PENGETAHUAN OBAT-OBATAN TRADISIONAL DALAM REZIM HAK KEKAYAAN INTELEKTUAL (HKI) INDONESIA (Studi Pada Masyarakat Tradisional Sasak) - Dwi Martini; Hayyanul Haq; Budi Sutrisno (Jurnal Hukum dan Peradilan, 2017)
In the modern context, the Traditional Medicine Knowledge (TMK) of Sasak community is a valuable economic asset considering its usage as a basic knowledge (milestone) in the modern medicine discovery. As a form of human intellectual ability, TMK is regulated under the IPRs-TRIPs regime, whereas TMK have prominent opposite characters with IPRs. This fact raises particular issues in terms of: the form of Sasak community’s TMK, regulation of its protection under the IPRs regime and the ideal legal institution to realize the protection. The majority of Sasak’s TMK are transmitted verbally, a fraction of it was written in babon (book of) tetamba/oat and lontar Usada. The IPRs-TRIPs regime only provides indirect regulation toward TMK, as contained in Patent and Plant Variety Protection Law. Ideally, there should be a local Law that particularly regulates protection on Sasak’s TMK in order to prevent misappropriation. Thus, there is a void of Law since there is no Sui Generis Law on the protection of TMK.Keywords: legal protection, traditional medicine knowledge, legal void